Conformal vector fields in symmetric and conformal symmetric spaces - Ramesh Sharma (International Journal of Mathematics and Mathematical Sciences)
Consequences of the existence of conformal vector fields in (locally) symmetric and conformal symmetric spaces, have been obtained. An attempt has been made for a physical interpretation of the consequences in the framework of general relativity.